The Effect of implementation of levels of inquiry on scientific reasoning and scientific attitude the senior high students on global warming topic - L Sopiyanti; S Anggraeni; M Nurjhani (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aimed to analyze the effect of implementation of levels of inquiry on thelearning material about global warming in order to increase the senior high students scientificreasoning and scientific attitude. This study used weak experimental method with one grouppretest-posttest. This study uses the senior high students as participants (N = 33) in theacademic year 2017/2018. Data were gathered levels of inquiry implementation observationprotocols, test on scientific reasoning, and questionnaire about the students scientific attitude.The category of scientific reasoning refers to Wenningand Vieyras framework. Scientificattitude indicators that were measured consists of six components. The average students gainon scientific reasoning is 0.35, which is categorized moderate. The effect size of 1.06 indicatesa large contribution. The students scientific attitude is 78.09 %, which is categorized positive.This result indicates that implementation of levels of inquiry on global warming topic has largecontribution to increase the scientific reasoning and scientific attitude the senior high students.